2016
DOI: 10.1177/1362361316638786
|View full text |Cite
|
Sign up to set email alerts
|

An international review of autism knowledge assessment measures

Abstract: Autism spectrum disorder-specific knowledge deficits contribute to current disparities in the timing and quality of autism spectrum disorder services throughout the United States and globally. This study conducted a systematic review of Western and International literature to examine measures used to assess autism spectrum disorder knowledge. This review identified 44 unique autism spectrum disorder knowledge measures across 67 studies conducted in 21 countries. Measures used in each study were evaluated in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 85 publications
2
43
0
Order By: Relevance
“…It was therefore interesting to see a number of studies on knowledge about ASD, primarily from one group in West Africa. The Knowledge of Childhood Autism Among Health Workers (KCAHW) was evaluated in the review by Harrison et al [], but was unfortunately found not to have very strong support for global use. Apart from knowledge, it is also important to consider skills and competencies [Liu et al, ].…”
Section: Professional Knowledgementioning
confidence: 99%
“…It was therefore interesting to see a number of studies on knowledge about ASD, primarily from one group in West Africa. The Knowledge of Childhood Autism Among Health Workers (KCAHW) was evaluated in the review by Harrison et al [], but was unfortunately found not to have very strong support for global use. Apart from knowledge, it is also important to consider skills and competencies [Liu et al, ].…”
Section: Professional Knowledgementioning
confidence: 99%
“…Increasing interest in the degree to which challenges associated with autism arise from societal misconceptions about and stigma toward autism has contributed to a growing body of research examining misconceptions of and stigma toward autism among people who are not autistic (e.g., Gray, 1993; Mak and Kwok, 2010; Campbell and Barger, 2014; Obeid et al, 2015; Harrison et al, 2017). This research, typically conducted with non-autistic college students, has found that greater knowledge of autism and high-quality personal connections with autism coincide with lower stigma toward autism (Nevill and White, 2011; Gardiner and Iarocci, 2014; Gillespie-Lynch et al, 2015; White et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This study builds upon a small but growing body of research using online surveys to compare how autistic and non-autistic people with diverse relationships to autism view how autism is represented and researched (Kapp et al, 2013; Pellicano et al, 2014a,b; Kenny et al, 2016; Fletcher-Watson et al, 2017) by administering measures that have been used with diverse types of non-autistic people internationally (e.g., Obeid et al, 2015; Harrison et al, 2017) to both autistic and non-autistic people with diverse relationships to autism.…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy measures. In the absence of a global knowledge tool with good psychometric properties [Harrison, Slane, Hoang, & Campbell, 2017], a short knowledge questionnaire was devised for the study and is available from the authors. The ASD knowledge questionnaire was administered before and after completion of the course.…”
Section: Methodsmentioning
confidence: 99%